Onomatopoeic Analysis in the Graphic Novel Brasta Seta by Wahyu Hidayatz - Siska Hardianti; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Onomatopoeia is an imitation of objects or events that are often used in comics and graphic novels. The approach used is an approach approach, this type of research includes library research and the method used is descriptive with research techniques namely hermeneutic techniques. Based on the research conducted, it can be concluded that the onomatopoeic functions contained in the graphic novel Brasta Seta by Wahyu Hidayatz include a) the onomatopoeic function of describing moods, there are 107 data examples: hahaha, hu uu uu, b) the onomatopoeic function gives an impression on the objects seen, heard or felt there were 30 data Examples: breg!, shhh, c) onomatopoeic function describes there are 42 data Example: aaaa!, pyang!, d) onomatopoeic function of actions or objects that produce sound 75 data examples: kukuruyuuk, nyit nyit nyit. (2) the onomatopoeic meaning found in the graphic novel Brasta Seta by Wahyu Hidayatz is contextual meaning. The meaning of a lexeme or word that is in a context, for example the onomatopoeia “dzzyyeeerrr!!!” the sound that emerged from the explosion in the market made the situation noisy. The onomatopoeic sound in the graphic novel is because there are objects that exist and are supported by context.